2020
DOI: 10.31234/osf.io/23mu5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural indicators of food cue reactivity, regulation, and valuation and their associations with body composition and daily eating behavior

Abstract: Exposure to food cues activates the brain’s reward system and undermines efforts to regulate impulses to eat. During explicit regulation, lateral prefrontal cortex activates and modulates activity in reward regions and decreases food cravings. However, it is unclear whether: (1) there are between-person differences in recruitment of regions associated with reward processing, subjective valuation, and regulation during food cue exposure—absent instructions to regulate; and (2) individual differences in activati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
(73 reference statements)
1
6
0
Order By: Relevance
“…When examining differences in the self-reported valuation of healthy and unhealthy foods, our results indicate that self-reported valuation of unhealthy foods is inversely related to real world healthy eating, but we found no relationship for the valuation of either food type with BMI. This finding echoes prior work demonstrating a relationship between unhealthy eating behavior and reactivity to unhealthy food cues (Tetley et al, 2009), and suggests that valuation may be an important factor underlying this relationship (Cosme and Lopez, 2020). Moreover, this highlights the importance of regulation strategies that target the devaluation of unhealthy foods, whether by reappraisal or other down-regulation strategies (Giuliani et al, 2014).…”
Section: Figure 4 | (A)supporting
confidence: 81%
“…When examining differences in the self-reported valuation of healthy and unhealthy foods, our results indicate that self-reported valuation of unhealthy foods is inversely related to real world healthy eating, but we found no relationship for the valuation of either food type with BMI. This finding echoes prior work demonstrating a relationship between unhealthy eating behavior and reactivity to unhealthy food cues (Tetley et al, 2009), and suggests that valuation may be an important factor underlying this relationship (Cosme and Lopez, 2020). Moreover, this highlights the importance of regulation strategies that target the devaluation of unhealthy foods, whether by reappraisal or other down-regulation strategies (Giuliani et al, 2014).…”
Section: Figure 4 | (A)supporting
confidence: 81%
“…Although it is not a given that psychological modularity necessitates neural modularity, this assumption has been preserved in many neuroscientific implementations of system-based theories (Shulman et al, 2016;Strang et al, 2013), despite evidence in adults that multivariate patterns reflect meaningful information about decision-making (Hampton & O'Doherty, 2007). Our univariate and multivariate results, somewhat surprisingly, respectively provide support for both modularity and population coding (Cosme & Lopez, 2020) specifically, results revealed that univariate NAcc and lPFC activity was associated with decision behavior, and also that pattern expression of a multivariate cognitive control (but not value) signature predicted decisions. The former (evidence of modularity) is surprising, given the limited support for neural modularity that prior studies have found (Erickson, 2001), whereas the latter (population coding) is notable because no prior studies, to our knowledge, have found evidence of such in the context of brain modeling decision behavior (i.e., using multivariate metrics to model behavior/cognition).…”
Section: Modularity and Population Coding In System-based Theories Of Decision-makingmentioning
confidence: 50%
“…In other words, the multivariate patterns code for a given psychological process whereas the univariate activity of the modules controls the intensity of the process. Indeed, such multidimensional coding schemes appear to support decision behaviors in monkeys (Zhang, Chen, & Monosov, 2019), and similar findings from human samples in other domains (eating behavior) further hint at the neural plausibility of a modular-population hybrid scheme (Cosme & Lopez, 2020). Further work could also examine whether there is a qualitative shift between coding schemes across development (Gee et al, 2013).…”
Section: Modularity and Population Coding In System-based Theories Of Decision-makingmentioning
confidence: 56%
See 1 more Smart Citation
“…Despite not being completely comprehensive, this approach still allowed for thorough investigation into the robustness of results. For all multiverse analyses, we constructed specification curves by ranking models by their beta estimates (ascending) for parameters of interest for interpretation and visualization [92][93][94][95][96] . Because specification choices were not preregistered, we did not conduct formal null hypothesis testing of specification curves.…”
Section: Multiverse Analyses and Specification Curvesmentioning
confidence: 99%